Treatment of Heart Failure With Mid-Range Ejection Fraction: A Summary of Current Evidence - Ma, Teng; Su, Yang; Song, Jing; Xu, Dachun (Frontiers in Cardiovascular Medicine, 2021)
Heart failure (HF) is a complex syndrome causing heavy burden in public health, and the modern objective assessment of it is based on the left ventricular ejection fraction (LVEF). In 2016, the European Society of Cardiology classified the transition phase with LVEF of 40% to 49% as heart failure with mid-range ejection fraction (HFmrEF) in an attempt to uncover the specific characteristics and treatment of these patients, which might recover or worsen to HFpEF or HFrEF respectively, or conversely from these two subtypes. Up to now, what is generally clear is that patients with HFmrEF would possibly get more benefits from some targeted therapies with HFrEF than those with HFpEF. This review summarizes what is known about the findings in the treatment of HFmrEF and discusses what should we do to better define the peculiar HF phenotype in the future.